The Influence of Employee Engagement and Creativity on Employee Performance Through Organizational Citizenship Behavior - Tanto Gatot Sumarsono; Aimi Anuar; Ainun Mardiah; Suatmo Pantja Putra (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
This research aims to determine the influence of employee engagement and creativity on employee performance through organizational citizenship behavior (OCB) at Bank Mandiri, Malang of Indonesia. The populations consisting of Teller, Customer Service, Branch Head and Loan Officer employees at Bank Mandiri in Malang of Indonesia. The data analysis method used in this research is structural equation modeling-partial least square (SEM-PLS) using Smart PLS version 3. This research used two stages of PLS calculation models, namely the measurement model (outer model) and the structural model (inner model). The results of this research show that employee engagement has a significant positive effect on employee performance, creativity has a significant positive effect on employee performance, OCB has a significant positive effect on employee performance. Meanwhile, employee engagement has no significant effect on OCB, and OCB significantly mediates the effect of creativity on employee performance. This research provides evidence for research that is still debating that employee engagement, creativity and OCB are able to influence employee performance positively and significantly. These findings are also able to provide important insights for Bank Mandiri employees in improving banking services. Keywords: Employee engagement, Creativity, Organizational citizenship behavior, Employee performance